YOU and YOUR CREDIT: Credit Scores - Michael S. Gutter; Joan P. Elmore; Travis P. Mountain (EDIS)
This document is FCS7233, one of the YOU and YOUR CREDIT series by Michael S. Gutter, Joan P. Elmore, and Travis P. Mountain. Published by the UF Department of Family Youth and Community Sciences, September 2008.